Human biomonitoring system in the Czech Republic - Černá, Milena; Spěváčková, Věra; Batáriová, Andrea; Šmíd, Jiří; Čejchanová, Mája; Očadlíková, Danuše; Bavorová, Hana; Beneš, Bohuslav; Kubínová, Růžena (International journal of hygiene and environmental health, 2007)
The human biomonitoring (HBM) is an integral part of Environmental Health Monitoring System in the Czech Republic since 1994. Selected biomarkers of the internal dose (heavy metals, PCBs) and cytogenetic analysis of peripheral lymphocytes as a biomarker of the exposure/effect to/of environmental genotoxic factors are systematically followed up in the blood and urine of adults (blood donors), in children aged 8 to 10 years, and in the breast milk of nursing mothers. Selected outputs documented the declining trend of blood lead levels, with the recent reference value of 80 mg/l for men, and the rising trend of blood selenium levels in adults, but not in children. PCBs and chlorinated pesticides in human milk show a long-term downward trend, but still higher than in neighbouring countries. The frequency of aberrant cells revealed a downward trend, but the increase obtained in the last monitored period needs to be explained. Further HBM activities are required to demonstrate the corresponding trends and to reduce human exposure and health risks.
Keywords: hodnocení rizik; Female; Polychlorinated Biphenyls; dítě; předškolní dítě; ženské pohlaví; monitorování životního prostředí; polychlorované bifenyly; Adolescent; mateřské mléko; lidé; Environmental Health; surveillance populace; Risk Assessment; Milk, Human; Male; chromozomální aberace; těžké kovy; Czech Republic; Child, Preschool; Population Surveillance; Environmental Monitoring; environmentální zdraví; vystavení vlivu životního prostředí; Česká republika; lidé středního věku; Child; mužské pohlaví; Environmental Exposure; Metals, Heavy; Middle Aged; mladiství; Chromosome Aberrations; Humans